2010
DOI: 10.3892/or_00000713
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of melanoma growth by the metabolic hormone leptin

Abstract: We have previously shown that melanoma cells proliferate in response to the metabolic hormones TRH and TSH. The objective of the present study was to test the hypothesis that a third metabolic hormone, leptin, serves as a growth factor for melanoma. Using western blotting, indirect immunofluorescence, and RT-PCR, leptin receptors were found to be expressed by human melanoma cells. In contrast, cultured melanocytes expressed message for the receptor without detectable protein. Melanoma cells responded to treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 25 publications
2
39
0
2
Order By: Relevance
“…However, no supporting or conflicting data on these earlier results on bladder cancer have been published to date. In the case of human breast cancer [52], ovarian cancer [53], prostate cancer [54] and skin melanoma [55], leptin was overexpressed in more than 80% cases of malignant tissues determined by immunohistochemistry techniques. In brain [56], breast [52], esophagus cancers [57], Ob-R was also overexpressed in more than 80% cases of malignant tissues according to immunohistochemistry results.…”
Section: Expression Of Leptin and Ob-r In Human Breast Cancer And mentioning
confidence: 99%
“…However, no supporting or conflicting data on these earlier results on bladder cancer have been published to date. In the case of human breast cancer [52], ovarian cancer [53], prostate cancer [54] and skin melanoma [55], leptin was overexpressed in more than 80% cases of malignant tissues determined by immunohistochemistry techniques. In brain [56], breast [52], esophagus cancers [57], Ob-R was also overexpressed in more than 80% cases of malignant tissues according to immunohistochemistry results.…”
Section: Expression Of Leptin and Ob-r In Human Breast Cancer And mentioning
confidence: 99%
“…Expression of the TSH-R protein was detected in a wide panel of melanocytic lesions including melanoma. TSH activated the mitogen-activated protein kinase (MAPK) pathway and stimulated proliferation of melanoma cells, however, not melanocytes (Ellerhorst et al, 2010). Furthermore, TRH at low concentrations stimulated melanoma growth but not melanocytes’ proliferation and its expression was increased in dysplastic nevi in contrast to benign nevi and was expressed in 63% of melanoma samples (Ellerhorst et al, 2006).…”
Section: Equivalent Of Hypothalamic-pituitary-thyroid (Hpt) Axismentioning
confidence: 99%
“…It is worth noting that epidemiological studies showed a positive correlation between obesity and melanoma incidence (16,17). Mouse melanoma models also showed that obesity promoted melanoma development and progression (18,19). Many factors may contribute to the effects of obesity on melanoma growth.…”
Section: Tumorigenesis Involves Constant Communication Between Tumor mentioning
confidence: 99%